A numerical analysis of GeO2-doped multi-step index single-mode fiber for stimulated Brillouin scattering. (30th April 2018) - Xiao, H; Ren, G; Dong, Y; Li, H; Xiao, S; Wu, B; Jian, S
Abstract: A numerical analysis of a GeO2 -doped single-mode optical fiber with a multi-step index core toward stimulated Brillouin scattering (SBS) based dual-parameter sensing applications is proposed. Adjusting the parameters in the fiber design, higher-order acoustic modes are sufficiently enhanced, making the fiber feasible for discriminative measurements of temperature and strain in the meantime. Numerical simulations indicate that the Brillouin frequency shifts and peak SBS efficiencies are strongly dependent on the doping concentration and the thickness of low-index ring in the proposed fiber. With appropriate structural and optical parameters, this fiber could support two distinct acoustic modes with comparable peak SBS efficiencies and well-spaced Brillouin frequency shifts. The sensing characteristics contributed by the dual-peak feature in the Brillouin gain spectrum are explored. Calculated accuracies of temperature and strain in simultaneous measurements can be up to 0.64 °C and 15.4 με, respectively. The proposed fiber might have potential applications for long-haul distributed dual-parameter simultaneous measurements.